Dampak Belajar Dari Rumah (BDR) dalam Perencanaan Karir Siswa - Fitri Aulia; Mujidaturruhil Millah; M. Musifuddin (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
This study aims to determine the impact of learning from home (BDR) in career planning for class XI MA NW Samawa students class XI MA NW Samawa and to find out the factores that influence the understanding of career planning during the BDR period. This research approach uses a qualitative approach with a case study method. The population in this study were students. .data collection techniques using observation techniques, interviews, and documentation. Based on the results of research on class XI students at the MA NW Samawa school, the results showed that the implementation of learning from home (BDR) had an impact on career planning for students in class XI MA NW Samawa. .it means that students experience obstacles in planning intensive career planning. Students lack information related to career planning, lack of understanding of students to know themselves, students' unpreparedness in planning their careers. .it means that students have not been able to plan their future careers, students have not understood the steps in career planning which include: recognizing talents, paying attention to interests, paying attention to values, paying attention to personality, and understanding their potential. .This study has proven that the implementation of learning from home (BDR) has an impact on career planning for class XI students at MA NW Samawa.